THE ROLE OF SATISFACTION AND TRUST ON REVISIT INTENTION DOMESTIC TOURIST TO BANJAR HOT SPRING - Mahardika, I Made Ngurah Oka; Citra, I Putu Ananda (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
This study seeks to explore the key factors that influence the likelihood of domestic tourists revisiting Banjar Hot Springs in Buleleng Regency. The primary variables under examination include service quality and destination image, with tourist satisfaction serving as a mediating factor and trust functioning as a moderating variable. Data was collected from 200 domestic respondents, and analysis was performed using Smart-PLS 3. The findings reveal that while service quality significantly influences satisfaction, it has a negative effect on revisit intention. Destination image is found to have a substantial impact on both satisfaction and revisit intention. Furthermore, tourist satisfaction positively influences revisit intention. Satisfaction also plays a key mediating role, enhancing the relationship between both service quality and destination image with revisit intention. Trust emerges as a pure moderator in the link between satisfaction and revisit intention, indicating its important role in strengthening the relationship.